2021
DOI: 10.3389/fonc.2021.670809
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Safety of Tumor Treating Fields (TTFields) Applied to the Torso

Abstract: BackgroundTumor Treating Fields (TTFields) therapy is a non-invasive, loco-regional, anti-mitotic treatment modality that targets rapidly dividing cancerous cells, utilizing low intensity, alternating electric fields at cancer-cell-type specific frequencies. TTFields therapy is approved for the treatment of newly diagnosed and recurrent glioblastoma (GBM) in the US, Europe, Israel, Japan, and China. The favorable safety profile of TTFields in patients with GBM is partially attributed to the low rate of mitotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
(55 reference statements)
3
15
0
Order By: Relevance
“…On the other hand, in the experiments by Li et al, who studied a range of TTFields frequencies from 100–1000 kHz, the inhibition ratio of HeLa cell growth decreased as the frequency was increased, with the maximal growth inhibition observed for 100 kHz TTFields [ 53 ]. Our results are consistent with their findings that, for the HeLa cell line, lower frequencies of TTFields are more effective at reducing cell counts and hindering cell division—a result that is likely, at least in part, due to cell morphology [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, in the experiments by Li et al, who studied a range of TTFields frequencies from 100–1000 kHz, the inhibition ratio of HeLa cell growth decreased as the frequency was increased, with the maximal growth inhibition observed for 100 kHz TTFields [ 53 ]. Our results are consistent with their findings that, for the HeLa cell line, lower frequencies of TTFields are more effective at reducing cell counts and hindering cell division—a result that is likely, at least in part, due to cell morphology [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…As far as we are aware, this is the only study to date that has investigated the effects of TTFields on MCF-10A cells. Although there have been many successful clinical trials with TTFields, and their in vivo safety has been established in several studies [ 21 , 54 ], there are limited data available on the effects of TTFields on normal cells. In the recent work of Ye et al, it was found that TTFields applied to normal brain organoids in vitro induced cell damage that could lead to apoptosis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal housing and anesthesia as well as array composition and placement procedure were previously described [ 24 ]. Male SD rats (age: 7–8 weeks; weight: 150–200 g; Envigo Ltd., Jerusalem, Israel) were inoculated with N1-S1 cells (50,000 suspension in 10 µL serum free DMEM medium, diluted 1:1 in Matrigel) into the left hepatic lobe.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the study the rats were housed in individual cages to prevent tangling of the wires connected to the device. TTFields (2.4 V/cm RMS; 150 kHz; Novo-TTF100L device) were applied continuously for 5 days through two pairs of perpendicular arrays placed around the tumor, each pair applying unidirectional TTFields for 1 s intermittently [ 21 , 24 ]. Device usage data were recorded to ensure animals successfully received therapy for ≥18 h/day, as per clinical recommendations for maximizing treatment benefits [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Even cells that exhibit rapid cell division such as those found in bone marrow or intestine are not affected as they are protected by high impedance of the bone, and slower replication times compared to cancerous cells respectively. 6 Tight junctions between epithelial cells at the blood-brain barrier (BBB) are known to inhibit the influx and efflux of many molecules to the brain. 7,8 This barrier can be overcome by taking advantage of the leaky vasculature surrounding brain tumours which leads to the accumulation of NPs in the tumour, via the Enhanced Permeation and Retention (EPR) effect.…”
Section: Introductionmentioning
confidence: 99%